Underlying microevolutionary processes parallel macroevolutionary patterns in ancient neotropical mountains - Dantas-Queiroz, Marcos Vinicius [UNESP]; Cacossi, Tami da Costa; Leal, Bárbara Simões Santos; Chaves, Cleber Juliano Neves; Vasconcelos, Thais N. C.; Versieux, Leonardo de Melo; Palma-Silva, Clarisse [UNESP] (Wiley, 2021)
Aim: Ancient climatic fluctuations are invoked as the main driving force that generates the astonishing biodiversity in ancient mountains. As a result, endemism and spatial turnover are usually high and few species are widespread amongst entire mountain ranges, precluding the understanding of origins of macroevolutionary patterns. Here, we used a species endemic to, but widespread in, one of the most species-rich ancient mountains in the globe to test how environmental changes acted on and how their macroevolutionary patterns were shaped. Location: Espinhaço Range, Eastern Brazil. Taxon: Vriesea oligantha species complex (Bromeliaceae). Methods: We compiled data for plastidial regions and nuclear microsatellites to assess genetic diversity, population structure, migration rates and phylogenetic relationships. Using temperature and precipitation variables, we modelled suitable areas for the present and the past, estimating corridors between isolated populations. We also implemented Bayesian demographic analyses to estimate ancient populations dynamics. Finally, we tested if population structure is driven by isolation by environment or by distance using a Bayesian modelling approach. Results: Our results showed that the intraspecific divergence events of V. oligantha are older than those associated with the latest Pleistocene climatic oscillations, supporting the view that Quaternary climatic fluctuations are key components for understanding its population differentiation processes. Species distribution modelling estimated corridors between populations in the past, as also shown in the demographic analyses, depicting a major spatial reorganization during colder climates. Besides, the high genetic structure estimated results from both models of isolation by distance and by environment. Main conclusions: V. oligantha is a remarkable model to test the effects of climatic oscillations over the biological community, since this species originated in the early-Pleistocene, prevailing over several cycles of climatic fluctuations until today. The estimated demographic dynamics of V. oligantha agrees with the species-pump mechanism, suggesting it as the main cause of speciation within the Espinhaço Range. Moreover, the phylogeographic patterns of V. oligantha reflect previously recognised spatial and temporal macroevolutionary patterns in the Espinhaço Range, providing insights into how microevolutionary processes may have given rise to this astonishing mountain biodiversity.
Keywords: approximate Bayesian computation; Bromeliaceae; campos rupestres; epiphytes; Espinhaço; interglacial refugia; phylogeography; species-pump; Vriesea